2007
DOI: 10.1177/0146621606295196
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dimensionality by Maximizing H Coefficient–Based Objective Functions

Abstract: Mokken scale analysis can be used for scaling under nonparametric item response theory models. The results may, however, not reflect the underlying dimensionality of data. Various features of Mokken scale analysis-the H coefficient, Mokken scale conditions, and algorithms-may explain this result. In this article, three new H-based objective functions with slight reformulations of Mokken scale analysis in the unidimensional and multidimensional cases are introduced. Deterministic and stochastic nonhierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In particular, those studies revealed that MSA does not function well in conditions in which the traits correlate (Mroch & Bolt, 2006; van Abswoude et al, 2004), or in which the items load on more than one trait (van Abswoude et al, 2004). Although those test conditions are the rule rather than the exception in empirical practice (van Abswoude, Vermunt, & Hemker, 2007), after publication of these articles, numerous researchers have still used MSA as a dimensionality assessment tool (e.g., Bech, Fava, Trivedi, Wisniewski, & Rush, 2011; Chen, Tseng, Hu, & Koh, 2010; Doyle, Conroy, McGee, & Delaney, 2010; Emons et al, 2010; Koster et al, 2009; Meijer et al, 2011; Ordoñez, Ponsoda, Abad, & Romero, 2009; Roorda, Houwink, Smits, Molenaar, & Geurts, 2011; Sousa et al, 2010). Furthermore, MSA is still recommended to assess unidimensionality (Sijtsma et al, 2011).…”
mentioning
confidence: 99%
“…In particular, those studies revealed that MSA does not function well in conditions in which the traits correlate (Mroch & Bolt, 2006; van Abswoude et al, 2004), or in which the items load on more than one trait (van Abswoude et al, 2004). Although those test conditions are the rule rather than the exception in empirical practice (van Abswoude, Vermunt, & Hemker, 2007), after publication of these articles, numerous researchers have still used MSA as a dimensionality assessment tool (e.g., Bech, Fava, Trivedi, Wisniewski, & Rush, 2011; Chen, Tseng, Hu, & Koh, 2010; Doyle, Conroy, McGee, & Delaney, 2010; Emons et al, 2010; Koster et al, 2009; Meijer et al, 2011; Ordoñez, Ponsoda, Abad, & Romero, 2009; Roorda, Houwink, Smits, Molenaar, & Geurts, 2011; Sousa et al, 2010). Furthermore, MSA is still recommended to assess unidimensionality (Sijtsma et al, 2011).…”
mentioning
confidence: 99%